Herodietic products from chicken meat - Galenko, Oleg; Holovachko, Valerii (My University, 2020)
At the Department of technology of meat and meat products, a group of pasty products with extended shelf life for herodietic nutrition of high biological value is being developed. The finished product allows to expand the range of domestic herodietic products, to enrich the daily diet with useful nutrients and dietary fiber that meet the physiological needs of the body and contribute to the preservation of health, efficiency and active creative longevity of man. На кафедрі технології м'яса і м'ясних продуктів розробляється група пастоподібних продуктів з подовженим терміном зберігання для героїдичного харчування з високою біологічною цінністю. Готовий продукт дозволяє розширити асортимент вітчизняних героїдичних продуктів, збагатити щоденний раціон корисними поживними речовини та харчовими волокнами, які відповідають фізіологічним потребам організму та сприяють збереженню здоров’я, працездатності та активного творчого довголіття людини.
Keywords: курятина; м’ясопродукти; білок; chicken; meat products; protein; кафедра технології м’яса і м’ясних продуктів